2023
DOI: 10.21037/atm-22-6016
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human angiotensin-converting enzyme 2 plays a protective role in mice with sepsis-induced cardiac dysfunction through multiple signaling pathways dependent on converting angiotensin II to angiotensin 1–7

Abstract: Background: Sepsis-induced cardiac dysfunction (SICD) is a common complication of sepsis and contributes to mortality and the complexity of management in patients with sepsis. Recombinant human angiotensin-converting enzyme 2 (rhACE2) has been reported to protect the heart from injury and dysfunction in conditions which involve increased angiotensin II (Ang II). In this study, we aimed to detect the effects of rhACE2 on SICD.Methods: A SICD model was developed in male C57/B6 mice by lipopolysaccharide (LPS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 109 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…In the early stage of sepsis, under the action of various pathogenic factors, a large number of inflammatory cells can be activated, leading to the interaction of the proinflammatory response and anti-inflammatory response, causing increased capillary permeability, which results in generalized edema and a large amount of pleural and abdominal effusion[ 17 - 19 ]. Persistent generalized edema and large pleural effusions can cause hypotension, hypoxemia, and microcirculation disorders, and sustained hypoperfusion of systemic organs can cause organ dysfunction and ultimately respiratory and circulatory failure[ 20 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of sepsis, under the action of various pathogenic factors, a large number of inflammatory cells can be activated, leading to the interaction of the proinflammatory response and anti-inflammatory response, causing increased capillary permeability, which results in generalized edema and a large amount of pleural and abdominal effusion[ 17 - 19 ]. Persistent generalized edema and large pleural effusions can cause hypotension, hypoxemia, and microcirculation disorders, and sustained hypoperfusion of systemic organs can cause organ dysfunction and ultimately respiratory and circulatory failure[ 20 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study suggested that exogenous supplementation with Ang (1–7) greatly ameliorates LPS-stimulated cardiac inflammation, apoptosis and dysfunction in mice [ 10 ]. More recently, administration of recombinant human ACE2 (rhACE2) to mice greatly attenuates LPS-stimulated activation of the NLRP3 inflammasome, NF-κB and p38 MAPK signals, inflammation, and increased Ang II and decreased Ang (1–7), which then protected against LPS-stimulated cardiac pyroptosis and dysfunction [ 50 ]. However, the significance of ACE2 in sepsis-induced hypotension and vascular dysfunction remains unclear.…”
Section: Discussionmentioning
confidence: 99%